Steps Toward Evaluation as Decluttering: Learnings from Hawaiian Epistemology - April Nakaima; Sanjeev Sridharan (The Evaluation Center at Western Michigan University, 2023)
This paper discusses one of the more contemporary challenges in development and in global health--lots of good ideas from well-meaning insiders and outsiders that end up cluttering both the physical and mental spaces of what can be loosely termed as "attempts" at development. Given the place-based nature of indigenous thought, we turn to Hawaiian epistemology at looking to insights for clarity on how one can negotiate interactions to declutter place and also confuse identity.  We believe that evaluation as a field can help in bringing greater recognition of the need for models of development and learning that respect the importance of de-cluttering.  Implications for a decolonized approach to evaluation are discussed